PRAS40 prevents development of diabetic cardiomyopathy and improves hepatic insulin sensitivity in obesity - Mirko Völkers; Shirin Doroudgar; Nathalie Nguyen; Mathias H Konstandin; Pearl Quijada; Shabana Din; Luis Ornelas; Donna J Thuerauf; Natalie Gude; Kilian Friedrich; Stephan Herzig; Christopher C Glembotski; et al. (EMBO Molecular Medicine)
Abstract Diabetes is a multi‐organ disease and diabetic cardiomyopathy can result in heart failure, which is a leading cause of morbidity and mortality in diabetic patients. In the liver, insulin resistance contributes to hyperglycaemia and hyperlipidaemia, which further worsens the metabolic profile. Defects in mTOR signalling are believed to contribute to metabolic dysfunctions in diabetic liver and hearts, but evidence is missing that mTOR activation is causal to the development of diabetic cardiomyopathy. This study shows that specific mTORC1 inhibition by PRAS40 prevents the development of diabetic cardiomyopathy. This phenotype was associated with improved metabolic function, blunted hypertrophic growth and preserved cardiac function. In addition PRAS40 treatment improves hepatic insulin sensitivity and reduces systemic hyperglycaemia in obese mice. Thus, unlike rapamycin, mTORC1 inhibition with PRAS40 improves metabolic profile in diabetic mice. These findings may open novel avenues for therapeutic strategies using PRAS40 directed against diabetic‐related diseases.